2011
DOI: 10.1371/journal.pone.0022188
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hainosankyuto, a Traditional Japanese Medicine, on Streptococcus pyogenes Infection in Murine Model

Abstract: Background Streptococcus pyogenes (S. pyogenes) causes various serious diseases including necrotizing fasciitis and streptococcal toxic shock syndrome. One serious problem observed recently with S. pyogenes therapy is attenuation of the antibiotic effect, especially penicillin treatment failure and macrolide resistance. Hainosankyuto, a traditional Japanese medicine based on ancient Chinese medicine, has been used for treatment of infectious purulent diseases in Japan. In this study, we investigated the protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Each blood sample was centrifuged, and the resultant serum was stored at −80°C until the day of assay (Minami et al, 2011).…”
Section: Preparation Of Blood and Bal Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Each blood sample was centrifuged, and the resultant serum was stored at −80°C until the day of assay (Minami et al, 2011).…”
Section: Preparation Of Blood and Bal Samplesmentioning
confidence: 99%
“…We determined the levels of serum and BAL cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and IgA during the course of infection in pneumococcus-infected mice treated with SSHT as described earlier (Minami et al, 2011). TNF-α, IL-1β, IL-6 (Biolengend Inc. CA.…”
Section: Assays To Determine Serum and Bal Cytokinementioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that topical applications of herbal extract prevent acute irritant murine contact dermatitis [1] and that oral administration of Cordyceps sinensis extract prevents cutaneous damages from Streptococcus pyogenes infection in an air pouch murine infection model [2]. Likewise, oral administration of Hainosankyuto reduces skin lesion size and increased survival rate in a Streptococcus pyogenes infected murine model [3]. Similarly, oral administration of the water extract of Astragalus membranaceus inhibits the development of atopic dermatitis-like lesions in a murine model [4].…”
Section: Introductionmentioning
confidence: 99%